2023
DOI: 10.1186/s12903-023-02752-2
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of permanent maxillary first molars evaluated by cone-beam computed tomography among a Yemeni population

Abstract: Background The study's objective was to use CBCT to ascertain the root and root canal anatomy of the permanent maxillary first molars in a Yemeni population. It was considered how gender affected the prevalence of root canal morphology. Methods A sample of 373 CBCT records of maxillary permanent first molars belonging to 373 Yemeni individuals (162 males and 211 females) aged between 12 and 65 years were included in this study. Using CBCT on the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Based on the research by Naseri et al [28], on maxillary first molars, there were no differences in canal configuration related to gender and age, as well as in the frequency of roots or the number of canals. Study on Yemeni [27] population on the same group of teeth also revealed no significant gender differences relating to the number of roots, as well as no gender predilection in complete fusion of teeth. They obtained the same conclusion with the variations of the root canals in context of Vertucci classification of root canals.…”
Section: Discussionmentioning
confidence: 81%
“…Based on the research by Naseri et al [28], on maxillary first molars, there were no differences in canal configuration related to gender and age, as well as in the frequency of roots or the number of canals. Study on Yemeni [27] population on the same group of teeth also revealed no significant gender differences relating to the number of roots, as well as no gender predilection in complete fusion of teeth. They obtained the same conclusion with the variations of the root canals in context of Vertucci classification of root canals.…”
Section: Discussionmentioning
confidence: 81%
“…Mheiri et al [ 21 ] reported that the proportions of type II, III, and IV in 418 teeth were 73.7%, l7.2%, and 19.1%, respectively. Mufadhal and Madfa [ 22 ] reported that the proportions of type II, III, IV, V, VI, VII, and others in 306 teeth were 30.4%, 28.1%, 13.7%, 6.9%, 8.2%, 2.6%, and 10.1%, respectively. These differences are probably attributed to the different regions, races, genders, or ages [ 1 , 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mufadhal and Madfa [ 22 ] reported that the proportions of type II, III, IV, V, VI, VII, and others in 306 teeth were 30.4%, 28.1%, 13.7%, 6.9%, 8.2%, 2.6%, and 10.1%, respectively. These differences are probably attributed to the different regions, races, genders, or ages [ 1 , 20 22 ]. Our results demonstrated that type IV MFMs constituted the highest proportion, accounting for 65.0%, followed by type III MFMs accounting for 30.9%.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the configuration of root canals in immature permanent teeth. The configuration of the root canal with complete root development has been extensively reviewed in the existing literature [13,[24][25][26]. Root canals can exhibit several different shapes in cross-section: round, oval, long-oval, ribbon-shaped or irregular [27].…”
Section: Discussionmentioning
confidence: 99%